IMPORTANCE OF CHANGE MANAGEMENT FOR BUSINESS SURVIVAL & GROWTH IN THE DYNAMIC BUSINESS ENVIRONMENT - Sharma, Ashish; Dutta, Hitakshi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose: The study explores the role of change management in ensuring business survival and growth within an increasingly dynamic and digitally driven environment. It investigates how leadership, employee adaptability, and technological integration collectively influence organisational resilience and competitiveness. Design / Methodology / Approach: A qualitative, exploratory design was adopted using secondary data drawn from peer-reviewed research (2019–2024). The study employed thematic analysis to identify key patterns linking change management with digital transformation, employee readiness, and customer engagement. Findings: Three core themes emerged: 1. Employee adaptability through reskilling and leadership support improves change acceptance. 2. Technological integration enhances operational efficiency and cost reduction. 3. Customer-centric transformation—aided by neuromarketing and analytics—strengthens satisfaction and loyalty. These themes reveal that effective change management acts as a dynamic capability that continuously aligns people, processes, and technology. Practical Implications: Organisations should invest in leadership development, digital infrastructure, and skill enhancement to embed change readiness. For developing economies, focused capacity building and policy support are essential to overcome digital and cultural barriers. Originality / Value: The paper presents an integrated model linking Change Management → Digital Transformation → Employee Adaptation → Business Growth, offering a structured framework for sustainable organisational transformation.